Complexes between STE5 and components of the pheromone-responsive mitogen-activated protein kinase module. - Marcus, S (1994)
We present genetic evidence for complex formation of STE5 and the STE11, STE7, and FUS3 protein kinases, the pheromone-responsive mitogen-activated protein kinase module of Saccharomyces cerevisiae. Interaction between STE5 and STE11 is not dependent on STE7, and interaction between STE5 and STE7 does not require STE11. The N-terminal regulatory domain of STE11 is both necessary and sufficient for interaction with STE5. Interaction between STE7 and STE11 is bridged by STE5, suggesting the formation of a multiprotein complex. We also demonstrate biochemical interaction between STE5 and STE11 by using a combination of bacterially expressed fusion proteins and extracts prepared from yeast. Our results suggest that STE5 is a scaffolding protein that facilitates interactions between components of the pheromone-responsive mitogen-activated protein kinase module. We further propose that such scaffolding proteins serve to inhibit cross-talk between functionally unrelated mitogen-activated protein kinase modules within the same cell.